Static and dynamic impact of high voltage direct current (HVDC) in AC power transmission system - Mohd Irwan, Mohd Salleh (2009)
High voltage direct current(HVDC) is very suitable for AC transmitting power over very long distances.It is more economical for long distances of transmitting of transmitting power. Since the cost of an HVDC transmission line is less than that of an AC line with the same capacity, the additional cost of converters for DC transmission is offset when the line is long enough. Studies show that it is advantageous to consider overhead HVDC transmission lines when the transmission distance is longer than 600 km. HVDC lines have no reactance and are capable of transferring more power for the same conductor size than AC lines. DC transmission is especially advantageous when two remotely located large systems are to be connected. The DC transmission tie line acts as an asynchronous link between the two rigid systems eliminating the instability problem inherent in the AC links.This project will determine or analysis the impact of load flow,fault and stability by using Power System Computer Added Design(PSCAD).So,the stability and load flow of the system can be determined.Load flow study are used to ensure that electrical power transfer from generator to consumer through the grid system is stable, reliable and economic.The result from this analysis can be used to make another research related to the power flow which familiar as power system stability analysis